Social Determinants of HIV-Related Stigma in Faith-Based Organizations - Coleman, Jason D. (Am J Public Health, 2016)
Objectives. To examine the association between social factors in faith-based settings (including religiosity and proximity to people living with HIV/AIDS) and HIV stigma. Methods. A total of 1747 congregants from primarily African American faith-based organizations of Project FAITH (Fostering AIDS Initiatives That Heal), a South Carolina statewide initiative to address HIV-related stigma, completed a survey. Results. Female gender (P = .001), higher education (P < .001), knowing someone with HIV/AIDS (P = .01), and knowing someone who is gay (P < .001), but not religiosity, were associated with lower levels of stigma and with lower odds of stigmatizing attitudes (P < .05). Conclusions. Opportunities for connection with people living with HIV/AIDS tailored to the social characteristics of faith-based organizations may address HIV stigma in African American communities.